2018
DOI: 10.1073/pnas.1720570115
|View full text |Cite
|
Sign up to set email alerts
|

Holo-lipocalin-2–derived siderophores increase mitochondrial ROS and impair oxidative phosphorylation in rat cardiomyocytes

Abstract: Lipocalin-2 (Lcn2), a critical component of the innate immune response which binds siderophores and limits bacterial iron acquisition, can elicit spillover adverse proinflammatory effects. Here we show that holo-Lcn2 (Lcn2-siderophore-iron, 1:3:1) increases mitochondrial reactive oxygen species (ROS) generation and attenuates mitochondrial oxidative phosphorylation in adult rat primary cardiomyocytes in a manner blocked by -acetyl-cysteine or the mitochondria-specific antioxidant SkQ1. We further demonstrate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…LCN2 is an important regulator in iron metabolism. 41 The ability of LCN2 to regulate iron metabolism depends on whether LCN2 is bound to iron-laden siderophores. 41 The ironloaded LCN2-siderophore (Holo-LCN2) serves as an iron donor and is required for delivery of iron to cells/tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCN2 is an important regulator in iron metabolism. 41 The ability of LCN2 to regulate iron metabolism depends on whether LCN2 is bound to iron-laden siderophores. 41 The ironloaded LCN2-siderophore (Holo-LCN2) serves as an iron donor and is required for delivery of iron to cells/tissues.…”
Section: Discussionmentioning
confidence: 99%
“…41 The ability of LCN2 to regulate iron metabolism depends on whether LCN2 is bound to iron-laden siderophores. 41 The ironloaded LCN2-siderophore (Holo-LCN2) serves as an iron donor and is required for delivery of iron to cells/tissues. On Figure 5 Intestinal sirtuin 1 (SIRT1) deficiency mitigates hepatic ferroptosis in the ethanol (E)-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that CR attenuates serum, liver, and hippocampus LCN2 levels in db/db and ob/ob mice 48,49 . As circulating LCN2 increases in patients with heart failure, the production of LCN2 in the heart increases 51 , and in vitro treatment of cardiomyocytes with LCN2 causes iron accumulation and oxidative stress through increased 24p3R expression 52,53 . LCN2 may also be related to LVH and heart failure 54 , serving as a risk marker for the progression of atherosclerosis due to LCN2-MMP9 complex formation 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Lcn2 does not only prevent iron from being used by microbes, but also can serve as a bona fide cellular iron supplier. This mode of action of Lcn2 has been observed in the heart as well . Evidence from different studies has unveiled different factors that influence Lcn2 regulation in the heart, such as inflammation, hypoxia and body mass index (BMI) .…”
Section: Potential Role Of Lipocalin2 (Lcn2) In Cardiac Iron Metabolismmentioning
confidence: 81%
“…Lcn2 in the heart can be produced by cardiomyocytes, but it seems that the major source of Lcn2 is infiltrating granulocytes, present especially during cardiac injury or stress . In any case, Lcn2 can enter cardiomyocyte cells where it increases intracellular iron and ROS levels in mitochondria, though it is still debatable if the latter occurs because of the release of iron from Lcn2‐siderophore complex or from siderophores itself or both . Lcn2 has been shown to mediate other important effects primarily seen during cardiac remodelling, such as cardiomyocyte size, cellular proliferation, apoptosis, fibrosis with the net effect being cardiac hypertrophy and failure .…”
Section: Potential Role Of Lipocalin2 (Lcn2) In Cardiac Iron Metabolismmentioning
confidence: 99%